(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article presents the integration of science for industrial safety purposes, and also studies the characteristics of dust emitted by cotton ginning plants and its impact on the environment. Abstract: The article presents the types of diseases caused by the impact on the human body of harmful substances emitted into the atmosphere at cotton ginning plants. The characteristics of dust emitted by the cotton ginning plant and its impact on the environment are studied.